Resveratrol-loaded lipid-based nanocarriers for topical delivery: Comparative physical properties and antioxidant activity - Wipada Samprasit; Phuvamin Suriyaamporn; Pornsak Sriamornsak; Praneet Opanasopit; Benchawan Chamsai (Elsevier, 2024)
Resveratrol (R) is an antioxidant that helps several aspects of aging skin. However, it is slightly soluble in water and unstable under light exposure, necessitating the use of suitable formulations for improved clinical efficacy. Therefore, this study aimed to prepare R-loaded lipid-based nanocarriers for topical delivery, i.e., nanostructured lipid carriers (NLCs) and nanoemulsions (NEs). R-loaded nanocarrier gels were further prepared to increase R loading. The comparative physical properties and antioxidant activity of nanocarriers were performed in terms of particle size, zeta potential, morphology, rheology, R content, in vitro release, antioxidant activity, cytotoxicity and stability. The results revealed that R was successfully loaded into NLCs and NE gels (NEGs), having different physical properties and antioxidant activity depending on the composition of lipid-based nanocarriers. R could be incorporated into NEs and the aqueous gelling phase, resulting in higher R loading. Furthermore, the gelling network was responsible for pseudoplastic flow behavior. The cumulative amount of R released from NEGs was significantly higher than that from NLCs due to the co-surfactant-like properties of NEGs, which resulted in smaller particle sizes. However, NLCs exhibited significantly more antioxidant activity and less cytotoxicity compared to NEGs. The stability of both nanosystems showed no significant change when stored at refrigerator temperature for over 3 months. In conclusion, the various compositions of lipid-based nanocarriers produced a range of physical properties and antioxidant activity. Nonetheless, these NLCs and NEGs have the potential to be nanocarriers for R, which has antioxidant properties for topical application.